Additional lime of CaO in rearing medium with salinity for growing of catfish Pangasius hypopthalmus - Hastuti, Yuni Puji; Djokosetiyanto, Daniel; Permatasari, Ide (Jurnal Akuakultur Indonesia, 2012)
Catfish juvenile quality improvements sought through the addition of lime to the availability of minerals in the body. Media maintenance is set at 4‰ salinity aims to reduce the level of osmotic work to reduce energy used for osmoregulation and can be allocated to the growth of catfish. Juvenile-sized fish used 2.59±0.02 cm and weights 0.13±0.01 g. Aquarium measuring 20×20×20 cm3 used 15 units, filled with water salinity of 4% as 6 L per unit, and added lime CaO appropriate treatment. During the study, the fish were fed with 28% protein content three times a day with FR 5%. Addition of CaO treatment dose 0 mg/L, 20 mg/L, 40 mg/L, 60 mg/L, 80 mg/L result in the survival rate of 100%, 100%, 100%, 96.29%, and 100% (p>0.05). The growth rate of daily weight 5.196%, 5.212%, 6.596%, 5.35% and 5.101% (p>0.05). Long absolute yield significantly different values are 1.451 cm, 1.518 cm, 1.964 cm, 1.71 cm, and 1.546 cm (p<0.05). During the study, the water quality is within the range that can be tolerated by catfish juvenile. The use of lime in the salinity of 4% is suggested as many as 40 mg/L CaO with the turnover of water every day and feeding enough.Keywords: CaO, salinity, growth, Pangasius hypopthalmus